2018
DOI: 10.1002/anie.201808913
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Phase Conversion of Four Stereoisomers into a Single Enantiomer

Abstract: Viedma ripening is an emerging method for the solid‐phase deracemization of mixtures of enantiomers. Up to now, the scope of the method has remained limited to molecules with a single stereocenter. We show here that this method can be extended to obtain a single enantiomer from a mixture of stereoisomers with two different stereocenters. In addition, we show that by using tailor‐made chiral additives, the conversion time can be reduced by a factor of 100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The above cited work inspired a group of Rutjes and Vlieg to probe into more complex 3,4-diarylsuccinimides 51 a, b, which bear two similar but different substituents at C3 and C4 (Scheme 21A). [70] Epimerization studies in CDCl 3 solution containing 5 mol% DBU revealed that under equilibrium cis-51 a was present in only 2%, ergo trans-51 a was more stable by 2.5 kcal.mol À 1 . In other words, the driving force of crystallization was not required in order to transform cis-51 a to its trans counterpart in this case.…”
Section: Reviews Ascwiley-vchdementioning
confidence: 99%
“…The above cited work inspired a group of Rutjes and Vlieg to probe into more complex 3,4-diarylsuccinimides 51 a, b, which bear two similar but different substituents at C3 and C4 (Scheme 21A). [70] Epimerization studies in CDCl 3 solution containing 5 mol% DBU revealed that under equilibrium cis-51 a was present in only 2%, ergo trans-51 a was more stable by 2.5 kcal.mol À 1 . In other words, the driving force of crystallization was not required in order to transform cis-51 a to its trans counterpart in this case.…”
Section: Reviews Ascwiley-vchdementioning
confidence: 99%
“…On the other hand, and irrespective of actual mechanism of racemization, limitations by poorly performing (or even achiral) catalysts in enantioselective asymmetric synthesis, starting from achiral precursors, could be overcome by combination with Viedma ripening in analogy to asymmetric autocatalysis in homogenous systems. [17,35e,41] Analogously, application to diastereoselective asymmetric synthesis would also be possible, required that epimerization of individual chiral centers is selectively controlled, [42] extending the conglomerate concept to diastereomorphs or "quasi-enantiomorphs" (e. g. RÀ S and RÀ R), and when these neither differ too much in solubility nor their monomers' relative stability in a given solvent, in order to allow Viedma ripening. As the more stable diastereomer is likely to be the less soluble one, these could be conflicting goals, probably hard to reconcile in practice.…”
Section: Discussionmentioning
confidence: 99%
“…One option is to conduct the deracemization in pure isopropanol (instead of the 1:1 mixture with heptane), thereby increasing the solubility, which is beneficial for the racemization rate (Figure ). In addition, more severe grinding, the use of temperature cycling, the application of chiral additives, or combinations of these are possibilities to speed up deracemization.…”
Section: Figurementioning
confidence: 99%